STRATEGI KOMUNIKASI OMBUDSMAN RI SULBAR DALAM UPAYA MENINGKATKAN PARTISIPASI MASYARAKAT DALAM PENGAWASAN PELAYANAN PUBLIK DI PROVINSI SULBAR - irfan irfan; Sukriansyah S Latief; Yusmaniza Yusmaniza (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2024)
This research aims to describe the communication strategy used by the Ombudsman RI of West Sulawesi Province in an effort to increase public participation in public services supervision in West Sulawesi. This research was conducted in the Office of Ombudsman RI of West Sulawesi Province which is located in Mamuju Regency, West Sulawesi Province. This research used qualitative approach with case study method. Data were collected through in-depth interviews, observation, and documentation. The results of this study indicate that the SIMBA PVL programme carried out to various regions can increase public participation in terms of accessing complaint services at the Ombudsman RI of West Sulawesi. Only there are still weaknesses in socialisation related to the procedures for receiving complaints through digital media which shows that public participation through this access is very low. The obstacles found are the lack of employees owned by the Ombudsman RI of West Sulawesi Province to oversee the entire Public Service sector in West Sulawesi and the demographic conditions and characteristics of the Complainant in West Sulawesi. While the supporting aspects found are the existence of communication and good relations between institutions and the solidity of the work team so that it has a positive impact on the Ombudsman in carrying out its duties and authorities in West Sulawesi Province. This study recommends that the Ombudsman RI of West Sulawesi continue to improve the report acceptance programme that can reach community access to areas that are difficult to reach with electronic communication in West Sulawesi and further examine the strategy of using digital media in terms of access to report acceptance in West Sulawesi.